Manipulation of Lactobacillus Probiotic Strains to Produce Heterologous Beta-Glucanase for Chickens - Sieo, Chin Chin (2004)
Application of enzymes as feed additives is common in the livestock industry, especially in poultry, to eliminate the antinutritional factors present in the diets of chickens. However, the efficiency of enzymes seldom achieves their desired effects because of destruction during feed processing and unsuitable conditions in the gastrointestinal tract. Thus, in the present study, investigations were carried out to evaluate the potential of 12 Lactobacillus strains as delivery vehicles for a heterologous β-glucanase enzyme in poultry. The 12 Lactobacillus strains used were L. crispatus I12, L. acidophilus I16 and I26, L. fermentum I24, I25, C16 and C17, and L. brevis I23, I211, I218, C1 and C10. The strains were found to exhibit resistance to chloromphenicol, erythromycin and tetracycline in varying degrees. The erythromycin resistance of L. acidophilus I16 and I26, and L. fermentum I24 and C17 could be cured by using novobiocin, and L. brevis C10 cured by using acriflavin. The chloromphenicol and tetracycline resistances of all the resistant strains were not eliminated even after prolonged curing in sublethal concentrations of individual or mixtures of curing agents such as novobiocin, ethidium bromide, acriflavin or SDS. Electrotransformation efficiency of the Lactobacillus strains was affected by growth phase, growth and recovery medium, cell density, electroporation buffer, buffer strength, plasmid concentration and electrical pulse. At optimized conditions, the strains were transformed at 103-104 transformants/μg plasmid DNA. The erythromycin susceptible wild-type strains (L. crispatus I12, L. brevis I23, I211 and I218, and L. fermentum I25) and cured derivatives (L. acidophilus I16C and I26C, L. brevis v C10C, and L. fermentum I24C and C17C) were then transformed at optimized conditions with plasmid pSA3b6, which carried a β-glucanase gene from Bacillus amyloliquefaciens. Five wild-type Lactobacillus strains, namely, L. crispatus I12, L. fermentum I25, L. brevis I23, I211 and I218 and a cured derivative, L. brevis C10C, which could retain the plasmid at a comparatively higher rate, were used for subsequent studies. The Lactobacillus transformants were found to secrete 32-52 U/ml of β- glucanase. Optimum activity of the enzyme was at 39 oC and pH 5-6. A loss of 0.4-1.6 U/generation of β-glucanase was observed when the strains were grown under nonselective pressure. PCR analyses of gastrointestinal samples of chickens fed transformed Lactobacillus strains revealed that the strains could not persist for more than 24 h in the gut. The β- glucanase activity detected in the jejunum and ileum of chickens fed transformed Lactobacillus strains was found to be 2-9.4 folds higher than those obtained from other intestinal sites. In the feeding trial, supplementation of transformed Lactobacillus strains to chickens significantly (P<0.05) improved the body weight by 2.5 %, and the feed conversion ratio by 1.0-2.6 %. In addition, the apparent metabolizable energy, digestibilities of crude protein and dry matter of feed were improved by 3.4 %, 5.9 % and 3.5 %, respectively. The intestinal fluid viscosity was reduced by 21-46 %. The relative weights of organs and intestinal segments (pancrease, liver, duodenum, jejunum, ileum, cecum and colon) were also reduced by 6-27 %, and the relative length of intestinal segments (duodenum, jejunum, ileum and cecum) was reduced by 8-15 %. Histological examination of the intestinal tissues showed that the jejunal villus height of chickens fed diet supplemented with transformed Lactobacillus strains was significantly (P<0.05) higher than those of chickens fed other dietary treatments. The transformed Lactobacillus strains were also found to reduce the time of feed passage rate by 2.2 h. vi The results of the present study showed that the Lactobacillus strains have the potential to be used as delivery vehicles for a heterologous β-glucanase enzyme in poultry.